1999
DOI: 10.1007/s004380050939
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 1-aminocyclopropane-1-carboxylic acid synthase genes controlling the ethylene level of ripening fruit in Japanese pear (Pyrus pyrifolia Nakai)

Abstract: The shelf life of Japanese pear fruit is determined by its level of ethylene production. Relatively high levels of ethylene reduce storage potential and fruit quality. We have identified RFLP markers tightly linked to the locus that determines the rate of ethylene evolution in ripening fruit of the Japanese pear. The study was carried out using sequences of two types of 1-aminocyclopropane-1-carboxylic acid (ACC) synthase genes (PPACS1 and pPPACS2) and a ACC oxidase gene (PPAOX1) as probes on 35 Japanese pear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 28 publications
(27 reference statements)
7
71
0
1
Order By: Relevance
“…h −1 during ripening (Itai et al 2002). Differences in the ethylene production were thought to be regulated mainly by differential expression of ethylene biosynthetic genes of ACCsynthase (Itai et al 1999;2002; Ripening behaviour of some attached and detached fruits Many fruits that belong to climacteric group such as apple and pear enter the climacteric phase soon after harvest but they might not ripe fully for weeks if left on the tree (Gerhardt 1947). The best example for such a differential behaviour is the avocado fruit.…”
Section: Fruit Ripeningmentioning
confidence: 99%
“…h −1 during ripening (Itai et al 2002). Differences in the ethylene production were thought to be regulated mainly by differential expression of ethylene biosynthetic genes of ACCsynthase (Itai et al 1999;2002; Ripening behaviour of some attached and detached fruits Many fruits that belong to climacteric group such as apple and pear enter the climacteric phase soon after harvest but they might not ripe fully for weeks if left on the tree (Gerhardt 1947). The best example for such a differential behaviour is the avocado fruit.…”
Section: Fruit Ripeningmentioning
confidence: 99%
“…Through PpACS1 protein, there are only one N-glycosylation site (PGSs; N in NxS/T motifs, positions 422) and cAMP-and cGMP-dependent protein kinase phosphorylation site (R 307 RMS 310 ). Sequence comparison revealed that PpACS1 shares the highest similarity (97% identity) with PcACS2b (El-Sharkawy et al, 2004) and pPPACS2 (Itai et al, 1999). It shares relatively high homology (96% identity) with MdACS3a-1 and MdACS3a-2, but relatively low homology (83-95% identities) with pPPACS1 (Itai et al, 1999) and other known plant ACSs (Fig.1).…”
Section: Structural Analysis Of the Ppacs1 Proteinmentioning
confidence: 97%
“…Sequence comparison revealed that PpACS1 shares the highest similarity (97% identity) with PcACS2b (El-Sharkawy et al, 2004) and pPPACS2 (Itai et al, 1999). It shares relatively high homology (96% identity) with MdACS3a-1 and MdACS3a-2, but relatively low homology (83-95% identities) with pPPACS1 (Itai et al, 1999) and other known plant ACSs (Fig.1). This conserved structure may be related to the maintenance of ACS functions for plant development.…”
Section: Structural Analysis Of the Ppacs1 Proteinmentioning
confidence: 97%
See 2 more Smart Citations